2011
DOI: 10.1007/s10646-011-0659-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing abalone growth inhibition risk to cadmium and silver by linking toxicokinetics/toxicodynamics and subcellular partitioning

Abstract: The purpose of this study was to link toxicokinetics/toxicodynamics and subcellular partitioning for assessing the susceptibility and the growth inhibition risks of abalone Haliotis diversicolor supertexta exposed to waterborne and foodborne cadmium (Cd) and silver (Ag). We reanalyzed published data on growth inhibition and subcellular partitioning associated with the present mechanistic model to explore the correlations among elimination (k (e)), detoxification (k (d)), and recovery (k (r)) rate constants and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
1
1
Order By: Relevance
“…Although air pollution from traffic exhausts was identified as a possible source of Cd (21), contribution from diets cannot be ruled out. Dietary intake is one of the important sources of exposure to Cd in the general nonsmoking population, especially in consumption of some foods such as rice, other crops, and shellfish (22)(23)(24)(25). The urinary Cd concentrations in our study population were higher than those reported in the third U.S. National Health and Nutrition Survey (geometric mean: 0.37 mg/g creatinine; ref.…”
Section: Discussioncontrasting
confidence: 53%
“…Although air pollution from traffic exhausts was identified as a possible source of Cd (21), contribution from diets cannot be ruled out. Dietary intake is one of the important sources of exposure to Cd in the general nonsmoking population, especially in consumption of some foods such as rice, other crops, and shellfish (22)(23)(24)(25). The urinary Cd concentrations in our study population were higher than those reported in the third U.S. National Health and Nutrition Survey (geometric mean: 0.37 mg/g creatinine; ref.…”
Section: Discussioncontrasting
confidence: 53%
“…It is undeniable that diet has a signi cant role in elevating metal concentrations inside the human body. Notably, some dietary components like vegetables, rice, sh, and other consumables have been identi ed as potential sources of metals such as cadmium, particularly among non-smokers and the wider population [49][50][51][52]. Diet, lifestyle, and habits, including smoking, sports, and everyday activities, can also affect metal exposure and cause oxidative stress.…”
Section: Discussionmentioning
confidence: 99%